KEANEKARAGAMAN JENIS BURUNG DI TAMAN HUTAN RAYA GUNUNG TUMPA SULAWESI UTARA - Kevin R. Sumbaluwu; Johny S. Tasirin; Reynold P. Kainde (Universitas Sam Ratulangi, 2020)
Gunung Tumpa Forest Park has an area of 206.6 ha and is located in twoadministrative areas, namely Manado City and North Minahasa, and there are various typesof land cover, primary forest, secondary forest and cultivation land. Diversity is acharacteristic of a community that is related to the number of species or the richness ofspecies and the abundance of species as a constituent of the community. This study aims toinventory and study the diversity of bird species and their variations based on land covertypes in Gunung Tumpa Forest Park. This research was conducted from February to April2020 using the point count method. The results of this study found 57 bird species from 26families with 1691 individuals, with a Shannon - Wiener index value of 3.10 as an indicatorof high bird species diversity in Gunung Tumpa Forest Park. Keywords : Birds, Bird species diversity, Mount Tumpa